Vegetation of the classes Hydrochari-Lemnetea Oberd. 1967 and Potametea Tx. et Prsg. 1942 in the Jegrička watercourse (The province of Vojvodina, Serbia) - Džigurski Dejana M.; Stojanović Slobodanka J.; Knežević Aleksa S.; Nikolić Ljiljana M.; Ljevnaić-Mašić Branka B. (Zbornik Matice Srpske za Prirodne Nauke, 2010)
The Jegrička, once a natural watercourse traversing the southwestern part of the Bačka region, has been turned into a canal, which became part of the main canal network of the hydro-system Danube-Tisza-Danube (Hs DTD). In its turn, the Hs DTD is part of the European waterway linking the North Sea to the Black Sea, i.e., part of the navigable Rhine-Main-Danube Canal. The watercourse is 65.4 km long and it is divided into three levels. The presence of the regulated and the nonregulated sections of the canal, frequent and abrupt changes in water level in the individual sections, different depths and surface water widths of the various sections and the fishpond constructed in the lower section cause considerable vegetation diversity. The vegetation comprises aquatic associations of the classes Hydrochari-Lemnetea Oberd. 1967 and Potametea Tx. et Prsg. 1942. The class Hydrochari-Lemnetea Oberd. 1967 includes the following phytocoenoses: Salvinio-Spirodeletum polyrrhizae Slavnić 1956, Ceratophylletum demersi (Soó 27) Hild. 1956, Lemno-Utricularietum vulgaris Soó 1928 and Hydrocharidetum morsus-ranae Van Langendonck 1935. The class Potametea Tx. et Prsg. 1942 includes the associations Myriophyllo-Potametum Soó 1934, Najadetum marine Fukarek 1961, Nymphaeetum albae Vollmar 1947, Nymphoidetum peltate (Allorge 1922) Oberd. et Müller 1960 and Trapetum natantis Müller et Görs 1960.